2018
DOI: 10.3389/fmicb.2018.01325
|View full text |Cite
|
Sign up to set email alerts
|

Non-pathogenic Escherichia coli Enhance Stx2a Production of E. coli O157:H7 Through Both bamA-Dependent and Independent Mechanisms

Abstract: Intestinal colonization by the foodborne pathogen Escherichia coli O157:H7 leads to serious disease symptoms, including hemolytic uremic syndrome (HUS) and hemorrhagic colitis (HC). Synthesis of one or more Shiga toxins (Stx) is essential for HUS and HC development. The genes encoding Stx, including Stx2a, are found within a lambdoid prophage integrated in the E. coli O157:H7 chromosome. Enhanced Stx2a expression was reported when specific non-pathogenic E. coli strains were co-cultured with E. coli O157:H7, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 69 publications
1
27
0
1
Order By: Relevance
“…In mice given a co-culture of O157:H7 and phage-resistant E. coli , minimal toxin was recovered in the feces, but with E. coli that were phage-susceptible, higher levels of toxin were found (46). However, it is clear that phage infection of susceptible bacteria is not the only mechanism by which the gut microflora affects Stx2 levels during infection (19, 20, 24, 26).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In mice given a co-culture of O157:H7 and phage-resistant E. coli , minimal toxin was recovered in the feces, but with E. coli that were phage-susceptible, higher levels of toxin were found (46). However, it is clear that phage infection of susceptible bacteria is not the only mechanism by which the gut microflora affects Stx2 levels during infection (19, 20, 24, 26).…”
Section: Discussionmentioning
confidence: 99%
“…E. coli 0.1229 produces at least two molecules capable of increasing Stx2a. The first is MccB17, a DNA gyrase inhibitor, shown to activate Stx2a production in an earlier study (24). This current study identified a second molecule localized to a 12.8 kb plasmid, and all genes necessary for production are found within a 5.2 kb region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations